Information System for Managing Incoming and Outgoing Mail at the Central Statistics Agency of West Sumba Regency - Bora, Emilia Krista; Janga, Adelbertus Umbu; Adis, Alexander (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
BPS West Sumba Regency still manages mail manually, facing issues of efficiency, transparency and accuracy. Manual processes risk document loss and recording errors. This research aims to identify problems and recommend an integrated information system. This innovation is expected to increase productivity, reduce errors, and speed up decision-making at BPS. Rapid Application Development (RAD) is a software development model that focuses on accelerating processing time. This approach combines object-oriented development methods and structured techniques to accelerate the process of creating a system or application. The research showed that the implementation of the new information system at BPS West Sumba Regency improved operational efficiency. Mail processing time dropped from 3 hours to 1 hour, and the error rate was reduced from 15% to 2%. User satisfaction increased from 60% to 90%, which had a positive impact on employee motivation. User satisfaction increased from 60% to 90%, which had a positive impact on employee motivation and collaboration. The system also strengthened and improved transparency.